2019
DOI: 10.35429/jsetm.2019.5.3.17.23
|View full text |Cite
|
Sign up to set email alerts
|

Creativity: learning style or teaching strategy?

Abstract: The present research on Creativity: Learning Style or Didactic Strategy? It aims to identify the impact of Learning Styles and Didactic Strategies on Creativity. Teachers should resort to practices that make them obtain good results, projecting a quality training, this leads to being an active person, with social activities that make the student have a good and increasingly better participation in the process of teaching-learning, where it is capable of transmitting a discipline to overcome difficulties. (Márq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies have examined the relationship of students' learning styles and creative thinking. Espericueta et al [28] found that students' learning styles and didactic strategies are considered to have an impact to students' creative thinking. Ozturk and Karakus [29] looked at the creative thinking abilities of junior high school students with different social backgrounds and learning styles and found that the achievements of learning outcomes in aspects of creative thinking skills for each learning style were different.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined the relationship of students' learning styles and creative thinking. Espericueta et al [28] found that students' learning styles and didactic strategies are considered to have an impact to students' creative thinking. Ozturk and Karakus [29] looked at the creative thinking abilities of junior high school students with different social backgrounds and learning styles and found that the achievements of learning outcomes in aspects of creative thinking skills for each learning style were different.…”
Section: Introductionmentioning
confidence: 99%